Gender Predilection in Post-Graduation among Dental House Officers in a Public Tertiary Care Hospital: Gender Predilection in Post-Graduation among Dental House - Shoaib, Ayesha; Danish, Syed Hassan; Haider, Ambreen Khurshid; Fahim, Nimrah; Perveen, Fauzia; Mahmood, Anum (Pakistan Journal of Health Sciences, 2025)
Pakistan is characterized as a developing nation with 25000 registered dentists. Confronting issues as the demand and dental needs are rising, so grasping the knowledge for career choices is vital. Objectives: To determine the Post-graduate career choices and factors involved in career selection by gender among dental house officers in a public tertiary care hospital. Methods: This cross-sectional study was conducted at the Dow University of Health Sciences, Karachi, for six months using a convenient sampling technique by Self-administered questionnaire after consenting from the administration and house officers while maintaining privacy and approval from the Ethical Review Board. A sample size of n=82 was calculated at 50% proportion keeping the confidence limit at 10 using Open Epi Software Version 3.01. House Officers were inducted except those who had a gap of more than one year after graduation. Using SPSS version 28.0, the mean and standard deviation for numerical data were calculated for categorical data.Results: There were 11 (13.1%) male and 73 (86.9%) female. Male 10 (90.9%) and female 64 (87.7%) opted for post-graduation. Both genders opted for Oral Surgery and Restorative dentistry. In male, 11 (100%) wanted clinical dentistry while 52 (71.3%) female wanted it, 9 (12.3%) health management, 3 (4.1%) academics, 2(2.7%) business rest were undecided. Conclusions: Clinical dentistry and FCPS exams were chosen irrespective of gender and marital status. Among female Oral Surgery and Restorative Dentistry while in males Oral Surgery, Restorative Dentistry and Orthodontics departments were favoured.